La igualdad de ingreso y el crecimiento económico: Un análisis aplicado a las regiones colombianas. (2021)
In the mark of the discussion actual in the development theory about the conflict or the complementary between the socials objebtics of efficiency and distributive justice, this work answer the question ¿What had the relation been between the economic grow and the equality of the rent in the regional development Colombian in the period 1985 - 1998?. 1 'he study start whit the understanding of economic grow as a phenomenon determinedfor factors endogenous and of social stability and for the structures of consumption standing. The work concludes that the inequality distribution of rent and the economics opportunities had been having negatives impacts in the dynamics of economic gro w of the Colombian regions.